A method for producing high lipophilic antioxidants noodle products - Voon, Phooi Tee; Mat Sahri, Miskandar; Lim, Wei Huei; Lai, Oi Ming; Tan, Chin Ping; Lai, Wee Ting (2013)
The present invention provides method on preparing noodle product regardless in any form which contain stable delivery of lipophilic antioxidants from the source of red palm olein. A solid state delivery system which is invented was introducedinto the noodle preparation steps. Noodles are prepared by mixing flour, water, red palm olein solid state delivery system and others ingredients into a dough. The dough can be shaped into noodles and precooked with steam. The fresh noodles are dried with a flow of high velocity air at temperature of between 30-110°C to moisture content less than about 15%. Once dried, the product can be packaged as a brick and the product can be stored at ambient temperature for long periods of time.